Factor Xa Inhibitors and Low Molecular Weight Heparins in Perioperative Surgical Thromboprophylaxis: A Network Meta-analysis - Bajpai, Vijeta; Patel, Tejas; Dwivedi, Priyanka; Kabi, Ankita; Mishra, Amrita; Sharma, Ravi Shankar; Gupta, Astha; Gangwar, Pradeepika; Agarwal, Richa; Kishore, Surekha (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2025)
Background Venous thromboembolism (VTE) prophylaxis is crucial for reducing the risk of deep vein thrombosis (DVT) and pulmonary embolism (PE). This network meta-analysis was carried out to determine the most effective intervention among selective Xa inhibitors and low molecular weight heparins (LMWHs) for perioperative surgical thromboprophylaxis in major abdominal, pelvic, lumbar spine, and lower limb surgeries. Methods A systematic literature search was conducted for randomized controlled trials (RCTs) comparing selective factor Xa inhibitors, LMWHs, and placebo as thromboprophylaxis agents in major abdominal, pelvic, lumbar spine, and lower limb surgeries. A Bayesian network meta-analysis was performed to compare all interventions for the risk of developing DVT, VTE, major VTE, total bleeding, and major bleeding. The surface under the cumulative ranking curves was used to rank all interventions. Results Of 1788 retrieved references, 42 RCTs comparing 11 anticoagulants were included. As compared to enoxaparin, the risk of DVT was significantly reduced in patients treated with fondaparinux [RR: 0.53 (95% CrI: 0.31, 0.93)] and rivaroxaban [RR: 0.42 (95% CrI: 0.27, 0.64)]; VTE in patients treated with bemiparin [RR: 0.09 (95% CrI: 0, 0.7)], edoxaban [RR: 0.43 (95% CrI: 0.18, 0.96)], fondaparinux [RR: 0.55 (95% CrI: 0.34, 0.91)] and rivaroxaban [RR: 0.56 (95% CrI: 0.34, 0.85)]; major VTE in patients treated with rivaroxaban [RR: 0.26 (95% CrI: 0.11, 0.6)]. According to the surface under the cumulative ranking curves (SUCRA) value, fondaparinux and bemiparin increase the risk of serious bleeding more than other factor Xa inhibitors and LMWHs. Conclusion Rivaroxaban, fondaparinux, edoxaban, and bemiparin are superior perioperative thromboprophylaxis agents than enoxaparin in major surgeries. Fondaparinux and bemiparin have shown the highest risk of major bleeding compared to other factor Xa inhibitors and LMWHs.
Keywords: Factor Xa inhibitors